Pengaruh Price Discount, Free Shipping, Online Customer Review Terhadap Keputusan Pembelian Produk Gorden Melalui Shopee Di Solo Raya - Surya Chandra Mustaqim; Muhammad Syihabuddin (Journal of Innovative and Creativity, 2026)
This study aims to determine the effect of Price Discount (X1 ), Free Shipping (X2), and Online Customer Review (X3) on Purchase Decision (Y). The sample consists of 100 respondents who are customers of Toko Gorden Solo Raya on Shopee. Data were analyzed using multiple linear regression and hypothesis testing. The results of the t-test showed that Price Discount (t=2.135,p=0.035), Free Shipping (t=5.127,p=0.000), and Online Customer Review (t=2.163,p=0.033) partially had a positive and significant effect on Purchase Decisions. Simultaneously, the F-test results (F=76.570,p=0.000) confirmed a significant effect. The coefficient of determination (Adjusted R Square) was 0.696, indicating that these variables explain 69.6% of the Purchase Decision.